SYSTEMATIC LITERATUR REVIEW (SLR): PEMANFAATAN MEDIA SOSIAL SEBAGAI DAYA SAING WIRAUSAHA MUDA UMKM - Witri Shintia Amanda; Zuhrinal M. Nawawi (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the role of social media in improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), especially for young entrepreneurs, through a systematic literature review (SLR). This study examines the strategies and challenges faced by young entrepreneurs in utilizing social media to improve the competitiveness of MSMEs. This study also provides policy recommendations to encourage the use of social media for MSMEs, especially for young entrepreneurs. This study uses ten articles relevant to the research topic obtained from Google Scholar. This study found that social media has great potential in improving the competitiveness of MSMEs, such as expanding market reach, building brand image, and increasing interaction with customers. However, this study also shows challenges such as lack of digital knowledge and skills, limited resources, and changes in social media platform algorithms. This study concludes that to maximize the potential of social media for MSMEs, training and educational programs on digital marketing strategies, support from the government and related institutions, and close collaboration between MSME actors, the government, and non-profit institutions are needed.